A new thermoregulatory index for heterothermy. Issue 2 (27th November 2013) - Muñoz‐Garcia, Agustí; Ben‐Hamo, Miriam; Korine, Carmi; Pinshow, Berry; Williams, Joseph B.; O'Hara, Robert B.
Summary The controlled adjustment of body temperature (Tb) by animals in relation to ambient temperature (Ta), or heterothermy, is a phenomenon that has a clear adaptive value. Heterothermy results in a substantial reduction in energy expenditure and water loss, but it also incurs costs, such as the energy cost required for rewarming, energy cost of excretion of metabolic wastes, delayed development of offspring and fitness costs of increased vulnerability to predators. A general index quantifying heterothermy would be useful, since heterothermy is often correlated with important physiological variables that determine fitness. We used metabolic rate (MR), Tb and Ta to develop a thermoregulatory index (TRi), a continuous variable that describes the thermoregulatory effort of animals. TRi is expressed by an equation with two terms: the deviation of actual heat gain/dissipation to heat gain/dissipation predicted by first principles and the temperature dependence of metabolic reactions. TRi can be interpreted as a measure of the amount of time an animal needs to generate an amount of heat, estimated from physical principles, to reach a certain Tb along a temperature gradient. TRi eliminates the need to define a threshold for Tb and can be used to compare positions of animals along a thermoregulatory continuum within and among species of diverse taxonomic affiliation. In addition, TRi unveils the relationship between the energy expended for thermoregulation and important physiological variables that determine survival and reproduction. TRi requires knowledge of MR, which may be a disadvantage since information on MR for free‐living animals may be difficult to obtain. However, with the advent of methods to measure field metabolism, this impediment may be surmountable in many species.